(3QSGdI cJHgG GdTQja GdeWgQ Hf Ydi GdMSjfi Edi eTGjN Hfi gjKes - (3GdTQja GdeWgQ Hf Ydj GdMSjfjs
(3ChdgG (B:s
(3bO Yde GdOhSGSGOJi LYdfi Gddg aOGge hCWGd Yf GdfhGH hGdeMd GdeYehQ HGdehGgH s
(3BNQgG (B:s
(3Ohf GdfGS bGWHg eSJMVQkG Hc Whd GdOgQ hddCHO JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3eUOQ GbJfGA GdCUd (B:s
(3CeHQhRjGfG (B(10) s
Keywords: (3GdadSaI hGdefWbs